Corporate Social Strategy in Multinational Enterprises: Antecedents and Value Creation - Husted, Bryan W. (Journal of business ethics, 2007)
In this article, we examine the relationship of the multinational firm’s market environment, stakeholders, resources, and values to the development of strategic social planning and strategic social positioning. Using a sample of multinational enterprises in Mexico, we examine the relationship of these different ways of conducting social strategy to the creation of value by the firm. The market conditions of munificence and dynamism, and the resource for continuous innovation are found to be related to strategic social positioning. The social responsibility orientation of the firm is related to strategic social planning. Positioning is related to value creation for the multinational firm, but planning is not. We discuss the implications of these findings for research and practice.